An evaluation of teacher perceptions of the level 1 English Language teaching materials in Institute Teknologi MARA: a basis for course improvement / Caroline Kamini Thangiah - Thangiah, Caroline Kamini (1994)
In 1989, the Language Centre of ITM carried out major revisions to the English language teaching materials. The aim was to develop materials that would meet the growing needs of the students, the institute as well as the nation. But due to time and administrative constraints, the materials did not undergo any traffic. Thus the effectiveness of the materials is not known. The purpose of this study is to identify the strengths and weaknesses of the materials using teachers' perceptions in order that this might contribute to course improvement. The teachers' perceptions were explored in the following areas: objectives, content, approach, support and guidance and testing procedures. The design of the study consisted of a Materials Evaluation Questionnaire and teacher interviews. The subjects for this study were English language teachers from seven ITM branch campuses located in West Malaysia. The results of the study show that: (a) to a great extent the materials are not appropriate to the students, (b) to a great extent the materials are not adequate, (c) to a great extent the recommended communicative approach is successful with the students, (d) to a great extent the materials do not provide support and guidance for the teachers, (e) to a great extent the testing procedures are not effective in measuring student learning, (f) only to a certain extent the materials are stimulating, and (g) only to a certain extent the materials are successful in achieving the objectives of the course. The overall findings of the study support the recommendation for the improvement of the materials. Apart from providing recommendations for the improvement of the present Level I ELT materials, teachers also requested for training in areas such as materials development, ELT methodology, testing procedures and time and classroom management.